(untitled) (Annual of the Faculty of Philosophy in Skopje, 2019)
As a continuation of Aristotle’s definition of φρόνησις as a virtue by which the individual is competent in each individual case to find the optimal choice for action that in the background has the general picture of an eudaimonic life, in a specific medieval context, φρόνησις is treated also in the philosophy of St. Maximus the Confessor. According to St. Maximus the Confessor, φρόνησις is an understanding of practical matters that are related to active life, namely “the deliberative power that determines the right use of reason for those engaged in practice” (Amb Io. 1109B). In this text, the concept φρόνησις in the works of St. Maximus the Confessor through several aspects will be examined: creation as an expression of the Divine φρόνησις, φρόνησις within the systems of virtues and its function, φρόνησις as the basis for vita practica and the relation between vita practica and vita contemplativa. Through these thematic points, the characteristics of φρόνησις in St. Maximus Confessor’s works will be drawn, which will show his aspirations for reconciliation of microcosmic antinomies with the macrocosmic paradigm of the eternal Logos.